Are price limits on futures markets that cool? Evidence from the Brazilian mercantile and futures exchange - Marcelo Fernandes; Marco Aurelio dos Santos Rocha (Queen Mary University of London, Department of Economics, 2006)
This paper investigates the impact of price limits on the Brazilian futures markets using high frequency data. The aim is to identify whether there is a cool-off or a magnet effect. For that purpose, we examine a tick-by-tick data set that includes all contracts on the S\~AƒÂo Paulo stock index futures traded on the Brazilian Mercantile and Futures Exchange from January 1997 to December 1999. The results indicate that the conditional mean features a floor cool-off effect, whereas the conditional variance significantly increases as the price approaches the upper limit. We then build a trading strategy that accounts for the cool-off effect in the conditional mean so as to demonstrate that the latter has not only statistical, but also economic significance. The in-sample Sharpe ratio indeed is way superior to the buy-and-hold benchmarks we consider, whereas out-of-sample results evince similar performances.
Keywords: C22; G12; G15; G18; 330; Cool-off effect; Futures markets; Magnet effect; Price limits; Transactions data; Termingesch\~AƒÂft; Limitpreis; Terminb\~AƒÂrse; Warenb\~AƒÂrse; Brasilien